The Effect of Functional Value on Continuous Purchase Intention among Millennial Consumers at Halal-Certified Japanese Eatery - Yuciko Ichwanda Yasera (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the correlation between consumption values, attitudes, and sustainable purchasing intentions among Muslim millennial consumers. Using a quantitative approach, data was collected from 225 respondents who were active on social media and had eaten at a halal-certified Japanese restaurant. Analysis using Structural Equation Modeling Partial Least Squares (SEM-PLS) showed that concerns about food safety, health awareness, as well as prestige, affordability, visibility, and emotional values had a positive influence on attitudes towards halal certification and sustainable purchasing intentions. Price values also significantly affect continuous purchase intentions, although they do not affect attitudes. These findings provide important insights for halal food business players, especially Japanese restaurant operators, to refine marketing strategies in attracting and retaining halal conscious consumers in Indonesia.